Multiple LTR-Retrotransposon Families in the Asexual Yeast Candida albicans - Goodwin, Timothy J.D.; Poulter, Russell T.M. (Genome Research, 2000)
We have begun a characterization of the long terminal repeat (LTR) retrotransposons in the asexual yeast Candida albicans. A database of assembled C. albicans genomic sequence at Stanford University, which represents 14.9 Mb of the 16-Mb haploid genome, was screened and >350 distinct retrotransposon insertions were identified. The majority of these insertions represent previously unrecognized retrotransposons. The various elements were classified into 34 distinct families, each family being similar, in terms of the range of sequences that it represents, to a typical Ty element family of the related yeast Saccharomyces cerevisiae. These C. albicans retrotransposon families are generally of low copy number and vary widely in coding capacity. For only three families, was a full-length and apparently intact retrotransposon identified. For many families, only solo LTRs and LTR fragments remain. Several families of highly degenerate elements appear to be still capable of transposition, presumably via trans-activation. The overall structure of the retrotransposon population in C. albicans differs considerably from that of S. cerevisiae. In that species, retrotransposon insertions can be assigned to just five families. Most of these families still retain functional examples, and they generally appear at higher copy numbers than the C. albicans families. The possibility that these differences between the two species are attributable to the nonstandard genetic code of C. albicans or the asexual nature of its genome is discussed. A region rich in retrotransposon fragments, that lies adjacent to many of theCARE-2/Rel-2 sub-telomeric repeats, and which appears to have arisen through multiple rounds of duplication and recombination, is also described.[The sequence data described in this paper have been submitted to the GenBank data library. Accession numbers are listed in Table 1 and in the Materials and Methods section.]
10.1101/gr.10.2.174